2014
DOI: 10.1200/jco.2013.51.2756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Communication Skills Training Program for Oncologists Based on Patient Preferences for Communication When Receiving Bad News: A Randomized Controlled Trial

Abstract: A CST program based on patient preferences is effective for both oncologists and patients with cancer. Oncologists should consider CST as an approach to enhancing their communication skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
216
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(230 citation statements)
references
References 26 publications
8
216
0
6
Order By: Relevance
“…Physicians with better communication skills were more likely to inquire the patients' concerns, encourage physical activity and setting goals (Cabana et al 2006), and were able to offer better emotional support, which resulted in lower depression scores reported by the patients (Fujimori et al 2014). Cals et al (2009) also found that better communication skills resulted in less unnecessary prescription of antibiotics.…”
Section: Communicationmentioning
confidence: 87%
“…Physicians with better communication skills were more likely to inquire the patients' concerns, encourage physical activity and setting goals (Cabana et al 2006), and were able to offer better emotional support, which resulted in lower depression scores reported by the patients (Fujimori et al 2014). Cals et al (2009) also found that better communication skills resulted in less unnecessary prescription of antibiotics.…”
Section: Communicationmentioning
confidence: 87%
“…While recent randomized controlled trials revealed that training improved oncologists' communication skills, patients' mental health, and patients' trust in oncologists [23,24], little is known about how oncologists obtain skills to manage their own discomfort with talking about death. Examples of practical ways may include, but may not be limited to, talking with colleagues and/or senior medical oncologists who have confidence in communicating EOL issues, rotating palliative care services such as home hospice programs during the oncology fellowship, sharing personal experiences of patients and their families who have received hospice care and perceived cexperiencing a good death, and normalizing death and dying by engaging in nonmedical activities such as reading humanistic books on death.…”
Section: Discussionmentioning
confidence: 99%
“…Physician behavior is difficult to change and may require a higherintensity activity. 34 Also, more recent data suggest that a strong physician recommendation may influence parents' vaccine choices in the short term. 35 Our intervention stressed the importance of physician recommendation, but focused more on long-term relationship building.…”
Section: Discussionmentioning
confidence: 99%